MYCN overexpression is associated with unbalanced copy number gain, altered nuclear location, and overexpression of chromosome arm 17q genes in neuroblastoma tumors and cell lines. Issue 10 (14th July 2015) - Kuzyk, Alexandra; Booth, Samuel; Righolt, Christiaan; Mathur, Shubha; Gartner, John; Mai, Sabine
<x xml:space="preserve">Abstract</x> MYCN amplification and MYCN overexpression are poor prognostic factors in neuroblastoma. Tumors with unbalanced chromosome arm 17q gain are often associated with MYCN amplification; however, the relationship between chromosome 17 copy number status and MYCN expression is not known. We investigated the relationship between MYCN expression and chromosome 17 copy number, nuclear location, and gene expression. By performing dual‐colored fluorescence in situ hybridization on 16 primary neuroblastomas, we found that those with unbalanced gain of 17q have high MYCN expression, those with no gain have medium expression, and those with numerical gain have low expression (P < 0.0001). We also found that the nuclear location of 17q correlates with chromosome 17 copy number status: copies in tumors with unbalanced gain and no gain of chromosome 17 occupy a more central location than those in tumors with balanced gain (P < 0.0001). We show that a more central nuclear location of 17q coincides with increased expression of genes found within this chromosome arm. To further understand the association between MYCN expression and chromosome 17, we overexpressed MYCN in two low‐expressing MYCN cell lines, SHEP and GIMEN. We found that both cell lines had an unbalanced gain of chromosome 17q, a more central nuclear location of the region and increased expression of the 17q genes. Therefore, this study indicates, for the first time, a functional relationship between MYCN overexpression and the gain of 17q in neuroblastoma. © 2015 Wiley Periodicals, Inc.